Stanniocalcin-1: A Novel Mediator in Diabetic Kidney Disease and Cardiovascular Disease - Souradip Mookerjee; Guy Whitley; Debasish Banerjee (Kidney International Reports)
Diabetes mellitus represents a group of metabolic diseases characterized by hyperglycemia from defects in insulin secretion, action, or both. The prevalence of type 2 diabetes mellitus, characterized by insulin resistance, has increased over time in the UK, and is the most prevalent cause of chronic kidney disease (CKD). Cardiovascular complications are a major cause of mortality for these patients.Stanniocalcin (STC), originally identified in bony fish as a hormone regulating calcium levels, has since been found in mammals, including humans. In fish, STC functions as an antihypercalcemic factor. Mammals possess 2 STC orthologues, STC-1 and STC-2, with STC-1 demonstrating significant sequence and functional conservation across species. Unlike fish, STC-1 is not normally present in the blood of healthy humans. However, it can be detected in certain conditions such as pregnancy, cancer, and CKD.In humans, STC-1 has diverse roles, including modulation of calcium and phosphate homeostasis, and it is implicated in kidney and cardiovascular protection. It has been reported that STC-1 has antioxidant, anti-inflammatory, and antiapoptotic activities, playing a role in renoprotection in diabetic nephropathy.This review explores the molecular biology of STC-1, its physiological functions, and its emerging role in GKDs, particularly diabetic and cardiovascular diseases. We highlight its potential protective mechanisms against hypercalcemia, its antioxidant and anti-inflammatory properties, and its cardioprotective properties in ischemia-reperfusion.Further research into STC-1 could provide new insights into therapeutic strategies for managing diseases characterized by calcium imbalance and lead to new treatments for the cardiovascular morbidity associated with diabetic kidney disease.